(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: Leprosy is a chronic infectious granulomatous disease caused by Mycobacterium leprae, with a prevalence rate corresponded to 0.2/10000. Skin and peripheral nerves are mainly affected exhibiting spectrum of clinical and histopathological features based on the immunological status of the individual. The diagnosis is made from adequate clinical information combined with histopathology. Aims: The aim of study to asses the clinical and histopathological features and there correlation in diagnosing the cases of leprosy. Materials and Methods: A cross-sectional study of 2 years was conducted on 99 cases of skin biopsies histopathologically diagnosed with leprosy. Adequate clinical history was obtained and biopsies were stained with hematoxylin and eosin and modified Fite Faraco stain. A clinicopathological correlation was then attempted along with statistical analysis. Results: Out of the total 99 leprosy cases, maximum cases (34.34%) belonged to third decade of life with Male to Female ratio of 1.75:1. About 58.59% of the total cases of leprosy showed decreased sensations and nerve thickening was seen in 79.80% cases. Clinically, 45.46% lesions were erythematous plaques. Borderline tuberculoid leprosy (31.68%) was the most frequently diagnosed subtype of leprosy. Evaluation of agreement and correlation between clinical and histopathological classification of leprosy showed an overall agreement of 57.57%. Correlation was more in stable poles i.e. TT tuberculoid pole (TT) and lepromatous pole (LL). Conclusion: Leprosy is still a prevalent disease which raises the concern about therapeutic approaches and various health programmes. It may not have a classical clinical picture always. Many factors contribute in clinicopathological discordance. Hence, diagnostic efficacy can be improved by clinic- histopathological corroboration which includes morphological examination of the skin lesion along with proper clinical history and correlation of these findings with histopathological examination findings.